2015
DOI: 10.7322/jhgd.103002
|View full text |Cite
|
Sign up to set email alerts
|

Child Development: Comparison Between Children Who Attend or Do Not Attend Public Daycare Centres

Abstract: Objective: To avaluate and compare the development of children attending public nursery school from their peers who remain only in the home environment. Methods: We performed an observational, cross-sectional study with 167 children aged between 11 and 57 months from Alto Vale do Jequitinhonha, Minas Gerais, Brazil. The subjects were divided into two groups (nursery and hom areas:e), homogeneous in age, gender, socioeconomic status, and maternal education. The development areas: personal-social, language, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Approximate results were also recorded in previous studies that used the same instrument. [19][20][21] However, similar studies have found sex interference in the performance of children submitted to DDST II, demonstrating that there tends to be a correlation between the sex of the child and the variable that designates the outcome stated by evaluation of devel-opmental areas. 21 This fact can be linked to the expectations that society has today in relation to different skills/ways of being of boys and girls, as well as the fact they develop faster than they do with regard to physical maturity 27 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Approximate results were also recorded in previous studies that used the same instrument. [19][20][21] However, similar studies have found sex interference in the performance of children submitted to DDST II, demonstrating that there tends to be a correlation between the sex of the child and the variable that designates the outcome stated by evaluation of devel-opmental areas. 21 This fact can be linked to the expectations that society has today in relation to different skills/ways of being of boys and girls, as well as the fact they develop faster than they do with regard to physical maturity 27 .…”
Section: Discussionmentioning
confidence: 95%
“…[2][3] In some Brazilian research studies, 7,10 approximately 40% to 46% of children presented development that was assessed as at risk and/or suspected of delay, but most research reveals a percentage close to the 20% range. [19][20] Among possible explanations for this variation could be the particular characteristics of the study population in Belém, Pará, Brazil. In this study, the selection of the sample involved children belonging to public and municipal services networks, which are generally comprised of children from lower-income families and living in unfavourable socio-economic conditions; therefore, presumably, these children are under the effects of poverty, which brings with it limitations to insuring their proper development.…”
Section: Discussionmentioning
confidence: 99%
“…A comparision was also made between these and children who are cared for in residential settings, where in these cases the infections are stronger, and in day care centers infections are milder. [15][16][17][18] However, Lee and Young concluded that all day care children are at constant risk from respiratory diseases, so these environments should provide simple prevention measures. 15 Regarding respiratory diseases, LaCross et al studied nontypeable Haemophilus influenzae (NTHi) in two children from a day care center cited in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Outrossim, uma parcela expressiva das creches públicas no Brasil apresenta uma infraestrutura precária e com dificuldades de adquirir alimentos para as crianças, tais fatos são fatores negativos para o desenvolvimento infantil 21 . No estudo observacional e transversal de Amaro et al 22 não foi identificado diferença significativa no atraso do desenvolvimento entre os grupos de crianças com idade de 11 a 57 meses que frequentam a creche e as que não frequentam, dados que se encontram em acordo com as crianças do presente estudo onde foi observada uma prevalência de 61% dentre as crianças que não frequentam creche pública 22 .…”
Section: Pediatriaunclassified